Diversity and evolution of polyketide biosynthesis gene clusters in the Ceratocystidaceae. Issue 9 (September 2018) - Sayari, Mohammad; Steenkamp, Emma T.; van der Nest, Magriet A.; Wingfield, Brenda D.
Abstract: Polyketides are secondary metabolites with diverse biological activities. Polyketide synthases (PKS) are often encoded from genes clustered in the same genomic region. Functional analyses and genomic studies show that most fungi are capable of producing a repertoire of polyketides. We considered the potential of Ceratocystidaceae for producing polyketides using a comparative genomics approach. Our aims were to identify the putative polyketide biosynthesis gene clusters, to characterize them and predict the types of polyketide compounds they might produce. We used sequences from nineteen species in the genera, Ceratocystis, Endoconidiophora, Davidsoniella, Huntiella, Thielaviopsis and Bretziella, to identify and characterize PKS gene clusters, by employing a range of bioinformatics and phylogenetic tools. We showed that the genomes contained putative clusters containing a non-reducing type I PKS and a type III PKS. Phylogenetic analyses suggested that these genes were already present in the ancestor of the Ceratocystidaceae . By contrast, the various reducing type I PKS-containing clusters identified in these genomes appeared to have distinct evolutionary origins. Although one of the identified clusters potentially allows for the production of melanin, their functional characterization will undoubtedly reveal many novel and important compounds implicated in the biology of the Ceratocystidaceae .